Characteristics of the colonic crypts in inflammatory bowel diseases - Kh. M. Akhrieva; A. S. Tertychnyy; N. V. Pachuashvili; L. S. Urusova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Purpose: to characterize changes in the colon crypts in colitis and to assess their significance in the morphological diagnosis of inflammatory bowel diseases (IBD). Materials and methods: colon biopsies were retrospectively reviewed in patients with IBD (30 patients with ulcerative colitis (UC) and 30 patients with Crohn's disease (CD)) and in 30 patients where the diagnosis of IBD was not confirmed (self-limiting colitis not related to IBD (non-IBD)). The age of the patients ranged from 19 to 53 years. In all cases, the diagnosis was established based on a combination of clinical, laboratory, and instrumental diagnostic methods. Multiple biopsies were obtained from all patients during colonoscopy. The processing of the material was carried out according to generally accepted methodology. All cases were scanned using the Aperio TC histological preparation scanner (Leica, Germany) and re-examined with an emphasis on crypt changes. Results: the crypt characteristics found during the study were divided into the following groups. The most frequently detected changes included inflammatory and destructive changes (98% of cases of IBD and 80% of cases of non-IBD). Atrophic changes in crypts were more often found in patients with non-IBD colitis compared with cases of IBD (30% in IBD and 53.3% in non-IBD; p=0.03). Significant differences in frequency were observed when dysregenerative changes in crypts were detected (76.7% of cases of colitis in IBD and 13.3% of cases in non-IBD; p<0.001). Crypt budding was more pronounced in patients with UC compared with CD (92% in UC versus 70% in CD), and a special variant of crypt changes, which we termed "serpentine," was found exclusively in patients with CD. Conclusion: crypt changes found only in patients with IBD, such as budding crypts, can serve as an important differential diagnostic criterion for the diagnosis of IBD. In the IBD group, the discovered serpentine crypts can help in making a differential diagnosis between UC and CD. Inflammatory and destructive changes are found with equal frequency in both cases of IBD and non-IBD colitis and therefore cannot be considered specific diagnostic signs.